A Single Glycan at the 99-Loop of Human Kallikrein-related Peptidase 2 Regulates Activation and Enzymatic Activity - Guo, Shihui; Skala, Wolfgang; Magdolen, Viktor; Briza, Peter; Biniossek, Martin L; Schilling, Oliver; Kellermann, Josef; Brandstetter, Hans; Goettig, Peter (The Journal of biological chemistry, 2016)
Human kallikrein-related peptidase 2 (KLK2) is a key serine protease in semen liquefaction and prostate cancer together with KLK3/prostate-specific antigen. In order to decipher the function of its potential N-glycosylation site, we produced pro-KLK2 in Leishmania tarentolae cells and compared it with its non-glycosylated counterpart from Escherichia coli expression. Mass spectrometry revealed that Asn-95 carries a core glycan, consisting of two GlcNAc and three hexoses. Autocatalytic activation was retarded in glyco-pro-KLK2, whereas the activated glyco-form exhibited an increased proteolytic resistance. The specificity patterns obtained by the PICS (proteomic identification of protease cleavage sites) method are similar for both KLK2 variants, with a major preference for P1-Arg. However, glycosylation changes the enzymatic activity of KLK2 in a drastically substrate-dependent manner. Although glyco-KLK2 has a considerably lower catalytic efficiency than glycan-free KLK2 toward peptidic substrates with P2-Phe, the situation was reverted toward protein substrates, such as glyco-pro-KLK2 itself. These findings can be rationalized by the glycan-carrying 99-loop that prefers to cover the active site like a lid. By contrast, the non-glycosylated 99-loop seems to favor a wide open conformation, which mostly increases the apparent affinity for the substrates (i.e. by a reduction of Km). Also, the cleavage pattern and kinetics in autolytic inactivation of both KLK2 variants can be explained by a shift of the target sites due to the presence of the glycan. These striking effects of glycosylation pave the way to a deeper understanding of kallikrein-related peptidase biology and pathology.